iProfile Kastam Diraja Malaysia - Kastam Diraja Malaysia ([Putrajaya] : Jabatan Kastam Diraja Malaysia)
i-Profile memberi penjelasan yang nyata mengenai Kastam DiRaja Malaysia serta sumbangan mereka terhadap keharmonian masyarakat, kestabilan negara dan perkembangan ekonomi global.
System requirements : Pentium III or higher processor, Windows 98 or above, 64MB RAM, super VGA 800x600 display, sound card, 32Xcd-rom drive and QuickTime 5 or higher
System requirements : Macintosh Power PC or higher, system 9 or higher, 64MB RAM, RGB 800 x 600 display, sound card, 32Xcd-rom drive and QuickTime 5 or higher
Keywords: Customs administration -- Malaysia